Ethnomathematics on Traditional Culture: A Bibliometric Mapping Analysis and Systematic Review on Database Scopus - Pradana, Kenny Candra; Rizki Putra, Aldi; Rahmawati, Yasinta (CV. Tripe Konsultan, 2022)
This study aims to map research trends related to ethnomathematics in traditional culture by collecting and analyzing articles taken from the Scopus database. This research is a Bibliometric research on the Scopus database, to study the structure and dynamics of the field of ethnomathematics. There are five stages carried out in this study, namely the determination of keywords, data search, article selection, data validation, and data analysis. We searched publications from the Scopus database using two keyword substrings: “Traditional Culture” (“Traditional” or “Culture”) and “Ethnomathematics”. These keyword searches were conducted in the Scopus Database in one day, March 25, 2022, to avoid a daily update bias as the database continues to collect and update data. 65 articles were retained for bibliometric mapping analysis and systematic review. Of the 65 articles that were defended from 1988 – 2022, it was concluded that there was an increasing trend of publications in the last 3 years (2020-2022).